Meningkatkan Keterampilan Membaca dengan Menggunakan Media Kartu Kata pada Pembelajaran Bahasa Indonesia di Kelas I SDN 56/I Desa Aro - Fitriani, Auliya; Tyastuti, Dwi; Hasanah, Shaqila Meitha; Kurnian, Fetiami Dwi (Lembaga Yasin AlSys, 2023)
Reading is a very important language skill. The purpose of this research is to improve Reading Skills by Using Word Card Media in Indonesian Language Learning in Class I SDN 56/I Desa Aro. The subjects of this study were class I students at SDN 56/I in Aro Village with a total of 25 students, 16 boys and 9 girls. This research was conducted in the even semester of the 2022/2023 school year. This research is Classroom Action Research which consists of 4 stages namely; planning, action, observation and reflection. The data collection technique was an initial reading skills test, teacher and student observations conducted by colleagues as collaborators and documentation as a means of support and can be used as archives as evidence of research implementation. The results of the study show that using smart card media can improve reading skills by using word card media. This is evidenced by the success of the learning process marked by an increase in classical student mastery in each cycle, namely the percentage of students who complete the first cycle is 68% and increases in the second cycle by 80%.